Pengaruh Penggunaan Box Power Ignition terhadap Performa Sepeda Motor Injeksi - Dimas Bagaskoro; Taufik Wisnu Saputra; Danar Susilo Wijayanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
This study aims to (1) determine the effect of voltage variations on the power ignition box on the torque and power of the Honda Scoopy motorcycle in 2017. (2) determine the effect of variations in the voltage on the power ignition box on the fuel consumption of the Honda Scoopy motorcycle in 2017. (3) Knowing the effect of voltage variations on the power ignition box on exhaust emissions of the Honda Scoopy motorcycle in 2017. (4) Knowing the best voltage variations on the power ignition box are on power torque, fuel consumption, and exhaust emissions of the 2017 Honda Scoopy. Engine performance, including power torque, fuel consumption, and vehicle exhaust emissions, will be obtained by the maximum vehicle engine if the combustion system works optimally. One way to maximize the combustion system is using a power ignition box. The research method used is experimental. The research data was obtained using a sample of Honda Scoopy motorcycles in 2017. The independent variable used a power ignition box with voltage variations of 14.4 V, 14.7 V, 15.0 V, 15.3 V, 15.6 V, and 15 .9 V. The dependent variable is the power torque using a Dynamometer, fuel consumption using stationary test and road test on predetermined roads, and exhaust emissions using a Gas Analyzer. The results of this study are: (1) The maximum torque is obtained at a voltage variation of 15.6 V of 9.57 N.m, an increase of 8.5% from the standard state. The maximum power is obtained at the 15.6 V voltage variation of 6.63 HP, up to 8.5% from the standard state. (2) The maximum fuel consumption for the stationary test was obtained at a voltage variation of 14.7 V of 4.25 ml/min, decreased by 0.18 ml/min. The increase in average fuel consumption is at a value of 4.55 ml/min. The maximum fuel consumption for the road test was found at a voltage variation of 14.7 V of 30 m/ml increasing to 15 m from the standard state. The average increase in fuel consumption was 24.93 m/ml from standard conditions. (3) The maximum CO (carbon monoxide) of 0.3% at a voltage variation of 14.4 V, down 0.11% from standard conditions. The maximum HC (hydro carbon) is 16.00 ppm at a voltage variation of 15.0 V, down 15.33 ppm from standard conditions. Maximum CO2 (carbon dioxide) is 2.0% at a voltage variation of 15.9 V, down 0.10% from standard conditions. The maximum O2 (oxygen) is 9.25% at a voltage variation of 15.6 V, down 3.23% from standard conditions. The best configuration for the Box Power Ignition is at a voltage of 15.3 V.Keywords: Honda Scoopy, Box Power Ignition, Torque and Power, Fuel Consumption, Exhaust Emissions.